Educators’ Reasons for Not Practising 2SLGBTQ+ Inclusive Education - Campbell, Christopher; Peter, Tracey; Taylor, Catherine (Canadian Journal of Education / Revue canadienne de l'éducation, 2021)
In this article, we analyze educators’ self-reported reasons for not addressing LGBTQ topics in their schools in order to develop a clearer picture of the barriers that prevent educators from engaging in LGBTQ-supportive practices. Using hierarchal OLS (ordinary least squares) and logistic regression models to analyze the impacts of demographic, individual-based, and school-based barriers to practising LGBTQ inclusive education, we found that the most common reasons for inaction reported by educators were a lack of training/resources and general fear of opposition from various sources; however, educators who felt  that confidence in the level of support for LGBTQ-inclusive education at the school level were less likely to give these as reasons for inaction.